THE USE OF GALLERY WALK TOO ENHANCE THE SPEAKING ACHIEVEMENT OF THE NINTH GRADE STUDENTS OF SMP PGRI 1PALEMBANG - Hendri Dinata (Global Expert: Jurnal Bahasa dan Sastra, 2017)
The purpose of this study was to find out whether or not there is a significant difference on the ninth grade students’ speaking achievement who were taught by using Gallery Walk strategy and those who were not at SMP PGRI1 Palembang. The population of this study consisted of 154 ninth grade students of SMP PGRI1 Palembang in Academic Year of 2016/2017. There were 34 students taken as sample. Each group consisted of 17 students as experimental group and 17 students from class as control group. The sample of this study was taken by using purposive sampling method. In this study, the researcher used pretest-posttest non-equivalent group design. The instrument used in collecting the data was oral test in the form of presentation. The test was administrated twice as the pretest and posttest for both experimental and control group. The results of the test were analyzed by using IBM SPSS (Statistical Package for the Social Science) Statistics 21. The result showed that “there was means significant difference from students posttest score in experimental and control group, it was found the p-ouput (Sig.2-tailed) was lower than 0.05 level and t-obtained (12,505) is higher than t-table (1.756). So, the Ho (the null hypothesis)was rejected and Ha (the alternative hypothesis) was accepted. It means that there was significant difference on students’ listening comprehension achievement taught using Gallery Walk strategy than students who were taught by using teacher’s strategy.Keyword: gallery walk, speaking achievement